Serum concentrations of acute phase proteins in goats and ewes with naturally acquired Staphylococcus aureus mastitis - Simplício, K. M.M.G. [UNESP]; Rocha, T. G. [UNESP]; Sanchez, D. C.C. [UNESP]; Cotrim, F. S. [UNESP]; Silva, P. C. [UNESP]; Fagliari, J. J. [UNESP] (FapUNIFESP (SciELO), 2017)
Serum protein concentrations, including acute phase proteins (APPs), of goats and ewes with naturally acquired Sthaphylococcus aureus mastitis were determined by means of SDS-PAGE electrophoresis to evaluate the relevance of these APPs as biomarkers of the disease in these species. Fifteen healthy goats and 5 goats with naturally acquired staphylococci mastitis, as well as fifteen healthy ewes and 5 ewes with staphylococci mastitis were submitted to daily blood sampling during 7 days. In goats, an increase of 570%, 125%, 621%, and 279% in serum concentrations of ceruloplasmin, fibrinogen, haptoglobin and a1- acid glycoprotein, respectively, was observed. In sheep the increase in serum concentrations of ceruloplasmin, fibrinogen, haptoglobin and α1-acid glycoprotein was of 337%, 90%, 461%, and 225%, respectively. Our results indicate that these APPs have considerable potencial as early and sensible biomarkers of mastitis caused by S. aureus in goats and sheep.
Keywords: Ceruloplasmin; Fibrinogen; Haptoglobin; α1-acid glycoprotein